The dynamics and determinants of South African exports - Steenkamp, Francois Karl (School of Economics, 2020)
The thesis generates a deeper understanding of the dynamics and composition of a middleincome country’s – South Africa – export structure, and the factors that are driving this evolution. The focus is the nature, composition and determinants of the extensive margin. Two key factors that shape export patterns are considered: endowments and trade policy. The thesis also systematically unpacks the nature of the relationship between export patterns and economic development, by critically appraising assumptions regarding this relationship that are implicit in South African economic policy. The broad contribution of this thesis is to explore the export patterns of a recently liberalised, natural resource rich, middle-income country, and examine the role that endowments and trade policy play in shaping these export patterns, particularly adjustments along the extensive margin. The middle-income context is of conceptual relevance, and thus contributes to the broader discussion on the developmental implications of evolving export patterns. Although no singular unified policy exists, the broad thrust of South Africa’s export strategy is to diversify its export structure toward manufacturing, targeting emerging economies and regional markets, and using trade policy as an instrument to facilitate the diversification of its export structure. Drawing on the theoretical and empirical literature, Chapter 2 sets out to critically appraise this broad policy stance and the assumptions behind it. By drawing on lessons from the literature, the chapter looks to provide policy guidance. Chapter 3 aims to gain an understanding of the dynamics driving the evolution of South Africa’s export structure in the post-apartheid period. The analysis provides a picture of the sources of export growth, and the dynamics driving changes in the composition of South Africa’s export structure along the product and destination dimensions. Zahler’s (2011) product variety style decomposition approach is used to decompose South Africa’s export growth along the intensive and extensive margins. This approach is augmented to measure whether growth along the intensive margin is driven by price or quantity effects. The extensive margin is a relatively important source of export growth, particularly entry into new geographic markets. The intensive margin is dominated by the price effect. Chapter 4 examines the role of endowments in shaping South Africa’s export structure, as well as its evolving export structure. The Baldwin (1971) cross-commodity regression approach is employed, and advanced along two dimensions: Firstly, the approach is extended from a static to a dynamic analysis, and secondly, from an industry- to a productlevel analysis. South Africa’s export structure reveals it to be natural-resource and labour abundant, yet paradoxically human capital abundant. Endowments are shown to play a role in shaping South Africa’s evolving export structure, with its export structure, paradoxically, becoming increasingly capital-intensive. South Africa, a middle-income country, is shown to occupy a ‘middle position’ between its trading partners, indicating that the relative endowments of a middle-income country, such as South Africa, play a role in shaping its export structure across trading partners. Chapter 5 considers the role of tariff liberalisation, emerging from the Trade, Development and Cooperation Agreement (TDCA), in driving the growth and diversification of South African exports into European Union (EU) country markets, specifically EU10 markets. The analysis tests whether the revealed trade effects are consistent with the theoretical predictions of the Besedeš & Cole (2017) heterogeneous firm model. To measure the trade effect, the triple difference-in-differences estimator from Frazer & Van Biesebroeck (2010) is adapted and employed. The analysis deals with the endogeneity concern by using the extension of EU membership as an exogenous shock to identify the effect of trade preferences on South African exports. The expansion of the EU provides a unique event whereby a trade agreement negotiated between two parties (the EU15 countries and South Africa) is extended unilaterally and exogenously to another party (the EU10 countries). The analysis reveals a positive aggregate trade effect. Consistent with the Besedeš & Cole (2017) model, both aggregate and extensive margin growth effects are stronger in differentiated product markets relative to homogeneous product markets. The tariff liberalisation has been effective in driving the diversification of South African exports into EU10 countries.